Problematic use of internet among Indonesia university students: psychometric evaluation of Bergen social media addiction scale and internet gaming disorder scale-short form - Pramukti, Iqbal; Nurmala, Ira; Nadhiroh, Siti R.; Tung, Serene En Hui; Gan, Wan Ying; Siaw, Yan-Li; Yang, Yung-Ning; Griffiths, Mark D.; Lin, Chung-Ying; Pakpour, Amir H. (Korean Neuropsychiatric Association, 2023)
Objective Social media addiction and internet gaming disorder may cause mental health problems among a minority of university students. The Bergen Social Media Addiction Scale (BSMAS) and the 9-item Internet Gaming Disorder Scale-Short Form (IGDS9-SF) are commonly used worldwide. However, they have not been translated or validated into Indonesian. The present study aimed to translate and validate the BSMAS and IGDS9-SF in an Indonesian context among young adults. Methods A multi-center, web-based cross-sectional study was conducted among 458 university students (74% female; mean age 22.5 years) in Indonesia from June to December 2021. The BSMAS and IGDS9-SF were translated into Indonesian. Internal consistency (using Cronbach’s α and McDonald’s ω) and factor structure (using confirmatory factor analysis) of the two instruments were examined. Concurrent validity of BSMAS and IGDS9-SF was examined using their correlations with two external concepts: nomophobia and psychological distress. Results Internal consistency of the Indonesian BSMAS and IGDS9-SF were both acceptable (Cronbach’s α=0.80 and 0.90; McDonald’s ω=0.86 and 0.92). Both instruments were unidimensional with good factor loadings (0.54–0.78 for BSMAS; 0.63–0.79 for IGDS9-SF). Moreover, BSMAS and IGDS9-SF had stronger associations with nomophobia (r=0.58 and 0.12; p<0.001) than with psychological distress (r=0.43 and 0.15; p<0.001).Conclusion The Indonesian versions of the BSMAS and IGDS9-SF had good psychometric properties in terms of linguistic validity, unidimensionality, and reliability. The findings indicate the tools are appropriate for assessing the risk of social media addiction and internet gaming disorder among university students in Indonesia.